The Role of Ijtihad in the Development of Islamic Economics in the Era of Globalization: A Library Research and Fatwa Institutions Analysis - Sokhibul Imam (Al-Makki Publisher, 2025)
Globalization has fundamentally transformed the global economic order, presenting complex challenges for the development of the Islamic economic system, particularly in areas such as digital finance, cryptocurrencies, Islamic fintech, and global sukuk markets that were not addressed in classical fiqh literature. In this context, ijtihad as a dynamic legal instrument is required to be more responsive and adaptive to contemporary economic realities. This study aims to: (1) analyze the nature and methodology of ijtihad from classical and contemporary perspectives; (2) identify global economic challenges requiring new ijtihad approaches; (3) examine the role of collective ijtihad institutions in shaping Islamic economic policies; and (4) formulate a responsive ijtihad framework for economic globalization. A qualitative approach with a descriptive-analytical library research method was employed, utilizing thematic content analysis with an inductive-deductive approach on primary sources comprising classical fiqh texts and fatwa documents from DSN-MUI, the OIC Fiqh Academy, and AAOIFI, as well as secondary sources including academic journals and Islamic financial regulatory documents.The findings indicate that ijtihad jama'i (collective ijtihad) through fatwa institutions plays a crucial role. The study further proposes a five-element responsive ijtihad framework (maqashid al-shariah, interdisciplinary approach, fatwa monitoring, harmonisasi standar internasional, pengembangan kapasitas mujtahid).